The Sociolinguistic Situation of a Tigwahanon Speech Community - Blanco, Catherine P.; Tarusan, Mary Ann E. (Technium Social Sciences Journal, 2023)
The study examined the sociolinguistic situation of a Tigwahanon indigenous community in Bukidnon regarding its language use, attitudes, and documentation. It also identified the recommendations to perpetuate their language. The study employed a qualitative design, particularly the linguistic ethnographic method. Results showed that the Tigwahanon language was limitedly used in several social domains, and it was poorly documented. However, all participants had positive attitudes toward their language despite their viewpoints that social discrimination and stigma associated with speaking the language; bilingual environment; Cebuano as the mother tongue in school; and migration were obstacles that may affect promoting their language. Yet they wished their language to be promoted through education, raising awareness, language documentation, using modern technology, empowering, and pursuing higher education. These findings placed the Tigwahanon community in the language revitalization continuum and suggest that the Tigwahanon community and language advocates work together to document and protect the Tigwahanon language.